2021
DOI: 10.7759/cureus.19148
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 Pandemic on Presentation of Patients With Diabetic Retinopathy in a Multitier Ophthalmology Network in India

Abstract: Objective: This study aimed to describe the demographics and clinical profile of patients with diabetic retinopathy (DR) presenting during the novel coronavirus disease 2019 (COVID-19) lockdown and unlock phases in India. Methods: This hospital-based cross-sectional study included patients presenting from March 25, 2019, to March 31, 2021. All patients who presented with DR were included as cases. The data were collected using an electronic medical record system. Results: In total, 88,012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Patients with diabetic retinopathy also tend to have uncontrolled glucose monitoring during lockdown. Therefore, the status of diabetic retinopathy would worsen and progress [ 21 ] to proliferative or advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with diabetic retinopathy also tend to have uncontrolled glucose monitoring during lockdown. Therefore, the status of diabetic retinopathy would worsen and progress [ 21 ] to proliferative or advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy advances in DR screening and diagnostic technologies were a recurrent theme across multiple studies [ 22 - 28 ]. A subset of articles scrutinized the impact of COVID-19 lockdowns on DR, with contributions from various nations, including Greece [ 29 ], Jordan [ 30 ], the United States [ 14 ], and India [ 31 ]. Furthermore, diverse perspectives emerged as the literature explored alternative strategies for fundoscopic imaging [ 32 - 35 ] and DR treatment and barriers [ 36 , 37 ] that hinder patients' adherence to follow-up care.…”
Section: Reviewmentioning
confidence: 99%
“…Greece [29], Jordan [30], the United States [14], and India [31]. Furthermore, diverse perspectives emerged as the literature explored alternative strategies for fundoscopic imaging [32][33][34][35] and DR treatment and barriers [36,37] that hinder patients' adherence to follow-up care.…”
Section: Table 1: Distribution Of Study Types In the Reviewed Literaturementioning
confidence: 99%
“…Karempela et al [12] also reported significantly fewer visits for retinal laser during this period and delays in care that led to poorer visual outcomes [13]. A large cross-sectional study in India observed an increase in patients presenting with proliferative diabetic retinopathy and significant visual impairment over the lockdown period compared to the previous year [14]. Chatziralli et al described how restricted access to hospital follow-up and treatment led to poorer visual outcomes and progression in PDR [15].…”
Section: Introductionmentioning
confidence: 97%